(untitled) (Marketing Journal, 2026)
This study evaluated the economic efficiency of fixed asset utilization in railway transport enterprises. The economic essence and practical application of fixed asset turnover, fixed asset intensity, and fixed asset profitability indicators were analyzed. The impact of freight transportation volumes and changes in the structure of fixed assets on efficiency performance was examined. Based on the findings, practical recommendations were developed to improve fixed asset utilization, enhance the effectiveness of investment resources, and strengthen the operational performance of railway transport enterprises. The results confirmed the importance of efficient asset management.